EFEKTIVITAS TEH DAUN KERSEN (Muntingia calabura linn.) SEBAGAI MINUMAN FUNGSIONAL PENURUN KADAR GLUKOSA DARAH - Ihlana Nairfana; I Ketut Suter; Bambang Admadi Harsojuwono (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2019)
The aim of this research was to find the best treatment in order to achieve kersen tea with the highestflavonoid content and was expected to decrease blood sugar levels. This research was conducted inthree stages. Stage I was qualitative anylisis of flavonoids, the leaf position, different flavonoidsextraction condition whether it was extracted in daylight or dark condition, and the sample:solvent ratiothat gives the highest flavonoids contents. Stage II was to find out the effect of temperature and dryingtime on total flavonoids, antioxidant activity, and hedonic test for color, taste and aroma. Stage III wasin-vivo test to determine the ability of kersen leaf tea to reduce blood sugar levels in hyperglycemicmice. Kersen leaves positively contained flavonoids after tested in quantitative and qualitative ways.Sample from middle leaves that was dried at 60oC for 60 minutes and was extracted in daylightcondition with the sample:solvents ratio of 1:10 gives the highest flavonoids contents (7,75 mg/gextract), highest antioxidant activity (IC50 of 54,82 ppm), and tea color that was preferred by panelist.Kersen tea was able to decrease high blood sugar level of hyperglycemic BALB/c mice from 272.1 mg/dLto 250.2 mg/dL, or by 8.04%.